Factors Associated with Duration of Untreated Psychosis - A Retrospective Study done in a Rural Medical College - Arushi Singh; M. Poonam; S. S. Krithishree; R. Annapoorna (Archives of Medicine and Health Sciences)
Background and Aim: Duration of untreated psychosis (DUP) is the measure of time from the emergence of the psychosis to intervention. There is a lot of controversy about its importance and the factors affecting the length of it. In this study, we investigate factors possibly affecting DUP in a patient’s attending psychiatry OPD in a rural medical college. Materials and Methods: This was a retrospective cross-sectional study. Cases were selected from the register of medical records identifying the occurrence of first-episode psychosis diagnosed with paranoid schizophrenia and delusional disorder according to the International Classification of Diseases -10 between July 2020 and July 2021. A total of 30 cases were included following approval from the ethical committee. These cases were investigated further for the factors of interest, i.e. sociodemographic details, substance abuse, family history, magico-religious beliefs, social support, and awareness of mental illness among caretakers. Results: The mean age of our sample (n = 30) was 32.7 years, and out of them, 53% were male, 53.3% of them were married, and maximum (53.3%) of them belonged to the age group of 18–29 years. The mean DUP among our patients was 13.27 weeks. 53.3% belonged to lower/upper lower socio - economic status, most of them (63.4%) belonging to rural background. 33.3% of the patients had family history of psychosis. Conclusion: Patient’s sociodemographic profile as well as social support, religious beliefs, and awareness of mental illness act as a predictor for the DUP. Therefore, the morbidity and stress of the caregivers can be reduced by identifying these factors and taking appropriate action.